1990
DOI: 10.1111/j.1432-1033.1990.tb19204.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the genes of two homologous intracellularly heterotopic isoenzymes

Abstract: The genes of mitochondrial and cytosolic aspartate aminotransferase of chicken were cloned and sequenced. In both genes nine exons encode the mature enzyme. The additional exon for the N-terminal presequence that directs mitochondrial aspartate aminotransferase into the mitochondria is separated by the largest intron from the rest of the gene. A comparison of the two genes of chicken with the aspartate aminotransferase genes of mouse [Tsuzuki, T., Obaru, K., Setoyama, C. & Shimada, K. (1987) J . Mol. Biol. 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The deduced amino acid sequence from pcAAT1 has been compared with those of other AATs from bacterial, vertebrate and plant species and (plastid-located, msaat2) [8], soybean AAT5 (plastid-located, soyaspam) [21], carrot AAT (cytosolic,Dcaat) [18], chicken mitochondrial (chickm) [13] and cytosolic (chickc) [13] AATs and E. coli AAT (Ecaat) [7]. Residue numbering is with respect to the N-terminal amino acid ofArabidopsis Ataatl.…”
Section: Comparison Of Ataatl With Aat Sequences From Other Speciesmentioning
confidence: 99%
“…The deduced amino acid sequence from pcAAT1 has been compared with those of other AATs from bacterial, vertebrate and plant species and (plastid-located, msaat2) [8], soybean AAT5 (plastid-located, soyaspam) [21], carrot AAT (cytosolic,Dcaat) [18], chicken mitochondrial (chickm) [13] and cytosolic (chickc) [13] AATs and E. coli AAT (Ecaat) [7]. Residue numbering is with respect to the N-terminal amino acid ofArabidopsis Ataatl.…”
Section: Comparison Of Ataatl With Aat Sequences From Other Speciesmentioning
confidence: 99%
“…Five of these introns are at the identical codon positions in the genes for cAspAT and mAspAT [16,29]. From these observations it was concluded that the introns were already in place before the divergence of the genes for cAspAT and mAspAT.…”
Section: Discussionmentioning
confidence: 93%
“…The dendrogram constructed with the neighbor-joining method [33] does not show antecedent divergence of plant cAspAT genes. Since the comparison of amino acid sequences of AspAT suggests that mAspAT genes have evolved more slowly than cAspAT genes [ 16,41], the low evolution rate of mAspAT genes could shift their place in the tree. It is thought that most aminotransferase proteins originate from a single universal ancestor protein and have diverged by early gene duplication and subsequent specialization for substrate specificity [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian mitochondrial AST has recently been reported to have kynurenine aminotransferase activity and play a role in the biosynthesis of kynurenic acid in rat, mouse and human brains (Han et al 2011). Studies on animal AST have shown that the cytosolic and mitochondrial isozymes are encoded by different but structurally related genes (Obaru et al 1988;Juretic et al 1990).…”
Section: Introductionmentioning
confidence: 99%